Particle Size, Mass Concentration, and Microbiota in Dental Aerosols. (July 2022) - Rafiee, A.; Carvalho, R.; Lunardon, D.; Flores-Mir, C.; Major, P.; Quemerais, B.; Altabtbaei, K.
Many dental procedures are considered aerosol-generating procedures that may put the dental operator and patients at risk for cross-infection due to contamination from nasal secretions and saliva. This aerosol, depending on the size of the particles, may stay suspended in the air for hours. The primary objective of the study was to characterize the size and concentrations of particles emitted from 7 different dental procedures, as well as estimate the contribution of the nasal and salivary fluids of the patient to the microbiota in the emitted bioaerosol. This cross-sectional study was conducted in an open-concept dental clinic with multiple operators at the same time. Particle size characterization and mass and particle concentrations were done by using 2 direct reading instruments: Dust-Trak DRX (Model 8534) and optical particle sizer (Model 3330). Active bioaerosol sampling was done before and during procedures. Bayesian modeling (SourceTracker2) of long-reads of the 16S ribosomal DNA was used to estimate the contribution of the patients' nasal and salivary fluids to the bioaerosol. Aerosols in most dental procedures were sub-PM1 dominant. Orthodontic debonding and denture adjustment consistently demonstrated more particles in the PM1, PM2.5, PM4, and PM10 ranges. The microbiota in bioaerosol samples were significantly different from saliva and nasal samples in both membership and abundance ( P  < 0.05) but not different from preoperative ambient air samples. A median of 80.15% of operator exposure was attributable to sources other than the patients' salivary or nasal fluids. Median operator's exposure from patients' fluids ranged from 1.45% to 2.75%. Corridor microbiota showed more patients' nasal bioaerosols than oral bioaerosols. High-volume saliva ejector and saliva ejector were effective in reducing bioaerosol escape. Patient nasal and salivary fluids are minor contributors to the operator's bioaerosol exposure, which has important implications for COVID-19. Control of bioaerosolization of nasal fluids warrants further investigation.